El Síndrome de Asperger y su clasificación - Zúñiga Montero, Marco Antonio (2009)
The article presents the Syndrome of Asperger that is a development generalized disorder. Its primary cause seems to be genetic and recently it was recognized as so by the scientific community. Due to its characteristics, this disease is little known by the population and even, for being of so recent discovery, many professionals of the educative, social and medical areas are not sufficiently informed on this subject. Many Costa Rican families present it. Traditionally, this syndrome is included within the autistic spectrum; nevertheless, it is contemplated in DSM IV as the Disorder of Asperger and in the CIE-10 as the Syndrome of Asperger. That classifies it as a clinical entity different from autism.